Catalytic and catalyst-free diboration of alkynes. Issue 11 (15th September 2017) - Zhao, Fei; Jia, Xiuwen; Li, Pinyi; Zhao, Jingwei; Zhou, Yu; Wang, Jiang; Liu, Hong
Abstract : The present review provides a comprehensive summary of the catalytic and catalyst-free diboration of alkynes. Abstract : The diboration of alkynes has become the most straightforward and powerful method for the synthesis of functionalized 1, 2-diborylalkenes, which are widely used as building blocks in organic synthesis. The present review provides a comprehensive summary of the diboration of alkynes, including platinum-, palladium-, cobalt-, copper-, iridium-, gold-, iron-, base- and small organic molecule-catalyzed diboration, direct and metal-free diboration, and base-promoted diboration of alkynes up to early 2017. The reaction conditions, regio- and stereoselectivities, and mechanisms are summarized in detail. Moreover, synthetic applications and perspectives on the diboration of alkynes are also discussed.